Rachunek "współistniejących" i "istniejących-w" a leibnizjańska metafizyka wyrażania - Berlioz, Dominique (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
The paper is devoted to some Leibniz's works concerning formal calculus, which makes use of so-called real sum operator. The author tries to show that the calculus had been created to articulate certain metaphysical intuitions specific for Leibniz. The calculus made it possible to put forth and to solve some problems unknown to the scholastic tradition.